A systematic review and meta-analysis of the diagnostic accuracy of rapid immunochromatographic assays for the detection of dengue virus IgM antibodies during acute infection - Stuart D. Blacksell (2018)
A meta-analysis of rapid (≤60 min) dengue diagnostic assays was conducted to determine accuracy and identify causes of between-study heterogeneity. A systematic review identified 302 potentially suitable studies, of which 11 were selected for meta-analysis. All selected studies evaluated the immunochromatographic test (ICT) manufactured by Panbio Pty Ltd. Individual study results for sensitivity ranged from 0.45 to 1.0, specificity 0.57-1.0, diagnostic odds ratio 4.5-1287, and positive:negative likelihood ratios 2.3-59 and 0.01-0.56, respectively. Results indicated that the ICT evaluated in the selected studies can both rule in and rule out disease but is more accurate when samples are collected later in the acute phase of infection. Limitations of this meta-analysis were significant between-study heterogeneity caused by inconsistencies in evaluation methodologies, and the evaluation of only the Panbio ICT. It is recommended that additional, standardized evaluations are required for other dengue ICTs. © 2005 Royal Society of Tropical Medicine and Hygiene.